Overview of Sino-Tibetan morphosyntax - LaPolla, Randy J. (Routledge, 2021)
At the earliest reconstructable stage of the development of the Sino-Tibetan (ST) language family, possibly as much as six thousand years ago (Thurgood 1994),1 the proto-language was monosyllabic. Matisoff (2014) reconstructs the syllable canon as *(P²) (P¹) Ci (G¹) (G²) V (ː) (w/y) (Cf) (s).2 It is not clear whether the prefixes in some or all cases entailed a vocalic element. If so, the structure might have been sesquisyllabic (e.g. as in the name təә̌rùng ‘T’rung/Dulong’, the vocalic element of the təә̌- prefix is very slight). There was no relational morphology (LaPolla 1990, 1992a,b, 1994b, 1995a,b, 2004), but there was derivational morphology in the form of prefixes, suffixes, and voicing alternations of the initial consonants (Wolfenden 1928, 1929; Benedict 1972; Pulleyblank 1962–3, 1972, 1973a,b, 1977–8, 1991, 2000; Bodman 1980; Mei 1980, 1988, 1989, 2012; LaPolla 1994c; Sagart 1999, Sagart & Baxter 2010, 2012; Jin 2008a-b; Gong 2000; Matisoff 2003; Handel 2012). In §1.1 are examples of several types of derivational morphology.3 Sections 1.2-1.5 discuss other aspects of morphosyntax common to all of Sino-Tibetan. Following that are sections that discuss aspects of the morphosyntax unique to Sinitic or Tibeto-Burman.